Editorial: Radicalism and Politics of Religion (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2008)
Radical Islamism has become the âsexiestâ issue in the international scholarship of religion since the September 11 tragedy in 2001. It has been associated with a number of terrorist attacks not only in the West but also in Muslim countries. Every single of radical Islamism has caught the interest of not only scholars and policy makers but also general public. Interestingly, the general assumption that religion is the source of peace has been seriously challenged, not by non-religious communities, but by the violent practices of particular religious groups, however small they are. Indeed, there are certain groups striving for Islam but by using acts which could give awful image on Islam itself and against humanity.